PERENCANAAN STRATEGIS SISTEM INFORMASI PERGURUAN TINGGI MENGGUNAKAN METODE WARD & PEPPARD Studi Kasus: STMIK Nusa Mandiri - Ade Christian (Universitas Bina Sarana Informatika Kota Sukabumi, 2014)
The development of information technology is very fast and can provide significant impact in all aspects of human life. This development led to the change of the role of technology in the world of business or organization. Information technology that does not support the needs of businessestoday need to be aligned with the strategy and objectives of the Organization so that the need to set up an outline of the strategic planning of information systems. The three main objectives of the efforts of the application of information system (SI) and information technology (it) within anorganization. The first, repair work efficiency by performing automation processes that manage information. Second, improve the effectiveness of management information in order to satisfy the needs with decision making. Third, improve the competitiveness or enhance the Organization'scompetitive advantage by changing style and way of doing business (Ward & amp; Peppard, 2002). The basic concepts used in drawing up the framework for strategic planning of information systems and information technology (SI/TI) at a College is the methodology put forward by JohnWard and Joe Peppard. Framework for strategic planning of information systems and information technology (SI/TI) proposed consists of 5 stages, namely: stage- 1-identification of the Organization, namely the stage-2: analysis of the business environment and information, stage-3SI/TI target, 4-stage determine strategic SI/TI and stage-5 is a plan and implementation. Analysis of the strategy of using the PESTEL analysis methods, analysis of BCG Matrix, an analysis of Porter's Six Force, SWOT analysis, Value Chain Analysis, analysis of the CSF and the BalancedScorecard.The results of the research is creating a framework of planning strategy that integrates TI SI/so it makes it easier for management to manage a resource to generate needed information, accurate, can be used jointly by all the parties.